Algal removal from raw water by electro-flotation - Jiang, Shuangcheng; Wang, Fuli; Lin, Feng; Du, Hong (Frontiers in Environmental Science, 2023)
In order to reduce the influence of algae on the conventional treatment process of the water plant, the electro-flotation process was used to test the raw water of a lake-type reservoir. After raw water with cyanobacteria as the dominant algae is treated by the best electro-flotation process, the average removal rate of algal density can reach 99.1%. The effects of current density, residence time, and electrode spacing on the algal removal efficiency of the electro-floating process were investigated by orthogonal experiments. The order of influence was current density > residence time > electrode spacing. Considering economics, the optimal process conditions were as follows: the current density was 5 mA/cm2, the dwell time was 6 min, and electrode spacing was 10 mm.